Caffeine and physical training: effects on cardiac morphology and cardiovascular response - Ruiz,Roberto (2014)
Objective to analyze the morphological structure of cardiac, blood pressure (BP), heart rate (HR) and heart rate variability (HRV) of rats subjected to physical training with supplementation of caffeine. Methods 60 rats were divided into 4 groups: control (CO), control with caffeine (CAF), trained control (TRE) and trained with caffeine (TCAF). All trained groups underwent 4 weeks of swimming, and all caffeine groups were supplemented by voluntary ingestion of caffeine diluted in drinking water. Results there were no changes to BP and HR between groups. Regarding HRV, there was a decrease in LFnorm (low frequency) and LF/HF ratio (low and high frequency) in TCAF and CAF compared to group (p<0.02 and p<0.03, respectively). An increase occurred in CAF compared to the CO in the component LFnorm (p<0.05). The results also showed an increase in the relative weight of heart in the TRE (p<0.04) and TCAF (p<0.03) compared to CO. Conclusion caffeine did not modify the hemodynamic responses. However, physical training resulted in a decrease in sympathetic response and an increase in relative heart weight.